What do Neurologists Need to Know About Psychiatry?. Issue 3 (1st June 2003) - Sharpe, Michael; Stone, Jon; Carson, Alan
Abstract : Avid journal readers will have come across an explosion of editorials about the need to build bridges between the specialities of neurology and psychiatry (Ross 2003; Baker et al. 2002; Cowan & Kandel 2001; Martin 2002). Indeed, the fact they became separated at all might be regarded as a historical accident, driven by early scientific understanding of the simpler parts of the nervous system on the one hand and the need to contain the disturbed behaviour of those with psychosis on the other, all underpinned by mind body dualism. What advantages could there be in breaking down the barriers? The authors of these editorials have focused on opportunities for increased scientific understanding of the neurobiological basis of subjective psychiatric phenomena. And as a topic for research, linked to the promise of neuroscience in general and functional brain imaging in particular, this is indeed a desirable endeavour. But what are the